Justification of the content and structure of the deontological competence of the educational manager - Zadorozhna-Knyagnitska, Lenina (ScienceRise: Pedagogical Education, 2018)
Nowadays exists a significant contradiction between the public need for improving the efficiency of management activities, increasing the requirements for the professional behaviour of managers in the changing conditions of the functioning of an educational institution as an open social system and the existing level of deontological readiness for professional management activities. The need for solving this controversy determines the development of the problem of deontological preparation of education managers, which should be investigated from the competence approach point of view, which allows allocating the meta-level of professional competence – the deontological competence of the education manager. The aim of the article is the substantiation of the meaning of the concept «deontological competence» and its components. To achieve the research aim, methods of theoretical analysis and generalization of actual scientific works of domestic and foreign researchers were used. It is determined that there are such approaches to defining the notion of «competence»: cognitive, systemic, functional, person-activity, multicomponent. The deontological competence of the education manager is defined as a complex subjective characteristic that determines his deontological readiness for management activity, the ability to have a suitable professional behaviour and make effective decisions. The emphasis is placed on the fact that deontological competence is a dynamic combination of deontological knowledge, practical skills, ways of thinking, professional, ideological and civic qualities, deontological values, which determines the ability of a person to carry out a proper professional behaviour and perform professional duty. It represents an integral characteristic of the education manager, defined by the requirements to him, the scope of his managerial functions, the conditions of management activities, ideas about its effectiveness.The structure of deontological competence as a unity of motivational-value, cognitive, technological components is substantiated. Conclusions and suggestions. The results of the study are the basis for developing a model of deontological preparation of education managers in universities, criteria and indicators for its effectiveness